Exploring the Correlation between Learning Motivation and Biology Achievement: A Study on Students of SMAN 7 Pangkep - Nurul Uswah; Ismail Ismail; A.Irma Suryani; Usman Usman; Nur Muhajirah Yunus (PT. Ininnawa Paramacitra Edukasi, 2024)
Motivation has a strategic role in a person's learning activities. Learning motivation is needed to foster interest in lessons, so that students are encouraged to learn. Learning outcomes are a manifestation of a student's process of motivating themselves in learning so that students have high learning outcomes where the student has a high level of mastery in receiving material from the teacher in the subject being studied. This research aims to determine the description of learning motivation and biology learning outcomes of students at SMAN 7 Pangkep. The type of research used is descriptive research using simple random sampling techniques. Data collection in this research used a learning motivation questionnaire and data on student learning outcomes was taken from odd semester exam results in the form of documentation where the data was processed in two ways, namely descriptive and inferential analysis. The data analysis technique uses a simple regression analysis test. The results of this research show that there is a positive relationship between learning motivation and student learning outcomes in biology learning with a correlation coefficient value of 0.487 indicating that the data obtained is in the medium category. The conclusion of this research is that there is a positive and significant relationship between learning motivation and the learning outcomes of class XI MIPA students at SMAN 7 Pangkep in biology learning. This means that the higher the student's learning motivation, the higher the learning outcomes. With motivation, students can develop activities and initiatives that can direct and maintain persistence in carrying out learning activities.